Separation of Chlorella biomass from culture medium by flocculation with rice starch - Choy, Sook Yan; Prasad, Krishnamurthy Nagendra; Wu, Ta Yeong; Raghunandan, Mavinakere Eshwaraiah; Phang, Siew Moi; Juan, Joon Ching; Ramanan, Ramakrishnan Nagasundara (Elsevier, 2018)
Coagulation-flocculation remains as one of the preferred methods for efficient harvesting of Chlorella sp. cells. Although the use of established aluminium salts is highly appraised for high harvesting efficiencies, excessive residual aluminium imparted on both the treated supernatant and harvested biomass remained worrisome. Hence, the objective of this present study is to minimize the resulting concentration of aluminium present in the system by evaluating the use of rice starch as an aid to chemical coagulants. The residual aluminium in the starch aided and non-aided treated supernatants and biomass were then determined by using an inductively coupled plasma-optical emission spectroscopy (ICP-OES) and energy-dispersive X-ray (EDX) spectroscopy respectively. At an optimum pH of 6, more than 95% of the initial Chlorella biomass was recovered at 72 mg/L of alum or 9 mg/L of PACl. However, high residual aluminium contents in treated supernatants (1.3–1.7 mg/L) and biomass (2.5–4.5% weight distribution) were evident. Through the introduction of autoclaved rice starch by up to 120 mg/L as an aid, the dosage of chemical coagulants applied and the detected residual aluminium concentrations were reduced by up to 54%. Despite the increment in organic loadings for these treated samples, the use of starch which is biodegradable would minimize the resulting toxicity and metal contamination imparted. Thus, rice starch can be considered as a potential alternative to lower the dependence on chemical coagulants which limits the reusability of culture medium. Based on the FE-SEM micrographs obtained, the resulting flocs treated with rice starch were notably filamentous and threadlike; in-line with the coagulation mechanism of adsorption and bridging.